Evaluation of Two Potential Biological Control Agents Against the Foxglove Aphid at Low Temperatures. Issue 1 (3rd January 2019) - Bellefeuille, Ymilie; Fournier, Marc; Lucas, Eric
Abstract: The foxglove aphid, Aulacorthum solani Kaltenbach (Hemiptera: Aphididae), has become a significant pest in horticulture as it can up build high populations from 10 to 18°C. Currently, chemical control is used as no commercially available biocontrol agent is effective at these temperatures. In this study, two potential biocontrol agents were evaluated: the silverfly, Leucopis glyphinivora Tanasijtshuk (Diptera: Chamaemyiidae), and the American hoverfly, Eupeodes americanus (Wiedemann) (Diptera: Syrphidae). Active flight, oviposition, and larval voracity were tested at 12, 15, and 18°C. The proportion of individuals demonstrating flight decreased at 12°C for the hoverfly and decreased at 15 and 12°C for the silverfly. Delay before active flight was greater for both species at 12°C. More hoverflies laid eggs after 7 d at all temperatures (12, 15, and 18°C) compared with silverflies. Hoverflies laid a higher number of eggs than silverflies at all temperatures. When given an additional 7 d at 12°C, oviposition increased for both species. Daily aphid consumption decreased as temperature decreased for both species, but average total aphid consumption did not decrease regardless of the temperature. This means that larval voracity for both the silvery and the American hoverfly was similar at all temperatures (12, 15, and 18°C) when considering aphid development. Hoverfly larvae consumed two times more aphids than silverfly larvae at all temperatures. This study demonstrates a clear superiority of the hoverfly over the silverfly at low temperatures and identifies it as a potential biocontrol agent of the foxglove aphid.